A general procedure for small-scale purification of fimbriae expressed by porcine enterotoxigenic escherichia coli strains (2008)
Fimbriae expression by enterotoxigenic Escherichia coli strains is a complex process which is controlled by global and local transcriptional regulators and post-transcriptional control. It is influenced by factors such as bacterial growth rate, culture medium composition, pH and temperature. Fimbrial expression could thus frequently become lost. Bacterial culture procedures favouring fimbrial expression are thus needed. The fimbriated bacterial population was therefore enriched by static culture in Mueller–Hinton broth. Fimbrial expression was then maintained by making it grow consecutively in agar CFA and Minca or minimal broth according to the fimbrial serotype. Maximum fimbrial expression was reached after 4h or 5h in culture. The fimbriae were extracted by heat -shock treatment and precipitated with 40% ammonium sulphate. Further purification was carried out by molecular exclusion and sodium deoxycholate treatment. This methodology integrates known procedures in a simple and reproducible process for obtaining F4, F5, F6 and F41 fimbriae in sufficient quantities for their subsequent use in producing antibodies, immunoassays and other studies (at laboratory level) requiring high-purity preparations (80%) to maintain their native structure. Key words: Enterotoxigenic Escherichia coli; fimbriae; Minca; minimal medium; CFA.